Optimal Coordination Method for an ADN With Multiple Network-Constrained VPPs - Ge, Chengyang; Lin, Shunfu; Li, Fangxing; Wang, Peng; Yang, Fan; Li, Dongdong (IEEE transactions on power systems, 2025)
This article proposes a multi-level operation framework for an active distribution network (ADN) with multiple network-constrained virtual power plants (VPPs). We consider the market clearing process, ADN and VPPs' profits, peer-to-peer (P2P) energy trading among and between the ADN and VPPs, and carbon trading to be functioning cooperatively under the energy and reactive power auxiliary service markets. Through this approach we have developed a multi-layer framework for the multi-VPP system by formulating bidding plans for the superior market operator and comprehensively issuing active/reactive incentive prices to the VPPs. In order to overcome the tractability of the solution, we transform the original multi-layer model into an equivalent single-level mixed integer linear programming (MILP) problem with Karush Kuhn Tucker (KKT) optimality conditions and a strong duality theorem. Through case studies based on the IEEE 33-bus test system we verify that the proposed method can effectively enhance system voltage security and will result in greater economic benefits to system participants.